The Maternal Role Performance among Indonesian Pregnant Adolescents - Erika, Erika; Boonyoung, Nongnut; Chunuan, Sopen (Journal of Research in Nursing-Midwifery and Health Sciences, 2017)
Adolescent pregnancy has become a common problem in the world and Indonesia. Pregnant adolescents Adolescent pregnancy has become a common problem in the world and Indonesia. Pregnant adolescents eliminate their ambition by taking responsibility as a mother. This study aimed to describe the maternal role performance in Indonesian pregnant adolescents during pregnancy. This was a descriptive qualitative study using in-depth interviews for data collection. The participants comprised 12 pregnant adolescents selected using purposive sampling. Data analysis was undertaken with the content analysis approach.Six themes of pregnant adolescents in performing maternal roles during pregnancy were found including: 1) taking care to stay healthy and safe during pregnancy, 2) maintaining a good relationship with husband and unborn baby, 3) seeking coping strategies to deal with psychosocial problems, 4) empowering husband to earn more money for maternal and unborn baby health, 5) seeking support to improve maternal and unborn baby health, and 6) creating happiness for herself. The findings are useful for nurse midwives or other health care providers to gain more knowledge tocreate appropriate strategies to improve pregnant adolescents’ abilities to perform their roles during pregnancy.